Performance of oil palm wood impregnated with phenolic resin at different concentrations and extended soaking periods - Ismail, Puteri Nur Khairunnisha (2015)
Wood from oil palm (Elaeis guineensis Jacq.) trunk has not yet been optimally utilized because of several imperfections in their properties. It was reported that the oil palm wood (OPW), even from the best outer-part, has four main imperfections, which are very low in strength (class III-V), very low in durability (class V), low in dimensional stability, and very poor in machining behavior. Considering these imperfections in properties, the properties of OPW should be improved before it can be utilized. Resin impregnation treatment has been considered as an effective method in overcoming the shortfalls of OPW mentioned above. The process of the treatment includes drying, impregnation, heating and densification. However, in this treatment, the resin used is not expected to penetrate and bulked into OPW cell walls. The soaking method has been used as a method for treating wood. It was reported that low molecular weight resin penetrates well into swollen cell walls that occurred by soaking method. Therefore, the impregnation and soaking process using low molecular weight phenol formaldehyde (Lmw-PF) were carried out in this study. The process consists of drying, impregnation, soaking process, semi-curing resin and curing to produce impreg OPW. Study was undertaken to determine the effect of soaking process and resin concentration on polymer loading and performance of impreg OPW which had been treated with Lmw-PF resin. The polygon sawing pattern was used to prepare the materials in this study. After drying to 15% MC, the lumber samples were impregnated under vacuum (80 mmHg) and continued with 30 min under pressure (120 psi) with resin concentration 10, 15 and 20%. After impregnation, the samples were soaked in a container contained with the same resin concentration for 6, 12, 18 and 24 h to allow soaking process. Then, the samples were re-dried in an oven set at a temperature of 70°C until 70% MC, before finally being fully cured in an oven at a temperature of 150°C for ±3 h. In general, the results from samples with soaking process (soaking periods at 6, 12, 18 and 24 h) were better than those without soaking process (soaking period 0 h). In terms of physical properties, the soaking periods and resin concentrations had a significant effect and had increment 4 times of density gain, 32.98% of weight percent gain, and 2 times cell wall penetration. The dimensional stability also give significantly effect to the impreg OPW. Both water absorption and thickness swelling had reduction on soaking periods and resin concentrations with 7.37% and 5.08% respectively. Meanwhile, in terms of mechanical properties, it was found that the soaking periods and resin concentrations gave significant effects and had increment 1.5 times of MOE, 2 times MOR, 2 times of compression strength parallel to the grain, 42.25% of hardness and 34% of shear strength parallel to the grain. The physical and mechanical properties of impreg OPW were positively correlated with polymer loading, whilst water absorption and thickness swelling were negatively correlated with polymer loading for impreg OPW.